Terrestrial-like zircon in a clast from an Apollo 14 breccia - Bellucci, J.; Nemchin, Alexander; Grange, M.; Robinson, K.; Collins, G.; Whitehouse, M.; Snape, J.; Norman, M.; Kring, D. (Elsevier BV, 2019)
A felsite clast in lunar breccia Apollo sample 14321, which has been interpreted as Imbrium ejecta, has petrographic and chemical features that are consistent with formation conditions commonly assigned to both lunar and terrestrial environments. A simple model of Imbrium impact ejecta presented here indicates a pre-impact depth of 30–70 km, i.e. near the base of the lunar crust. Results from Secondary Ion Mass Spectrometry trace element analyses indicate that zircon grains recovered from this clast have positive Ce/Ce? anomalies corresponding to an oxygen fugacity +2 to +4 log units higher than that of the lunar mantle, with crystallization temperatures of 771±88 to 810 ± 37 °C (2s) that are unusually low for lunar magmas. Additionally, Ti-in-quartz and zircon calculations indicate a pressure of crystallization of 6.9±1.2 kbar, corresponding to a depth of crystallization of 167±27 km on the Moon, contradicting ejecta modelling results. Such low-T, high-fO2, and high-P have not been observed for any other lunar clasts, are not known to exist on the Moon, and are broadly similar to those found in terrestrial magmas. The terrestrial-like redox conditions inferred for the parental magma of these zircon grains and other accessory minerals in the felsite contrasts with the presence of Fe-metal, bulk clast geochemistry, and the Pb isotope composition of K-feldspar grains within the clast, all of which are consistent with a lunar origin. The dichotomy between redox conditions and the depth of origin inferred from the zircon compositions compared to the ejecta modelling necessitates a multi-stage petrogenesis. Two, currently unresolvable hypotheses for the origin and history of the clast are allowed by these data. The first postulates that the relatively oxidizing conditions were developed in a lunar magma, possibly by fractional crystallization and enrichment of incompatible elements in a fluid-rich, phosphate-saturated magma, at the base of the lunar crust to form the zircon grains and their host felsite. Subsequent excavation by the Imbrium impact introduced more typical lunar features to the clast but preserved primary chemical characteristics in zircon and some other accessory minerals. However, this hypothesis fails to explain the high P of crystallization. Alternatively, the felsite and its zircon crystallized on Earth at a modest depth of 19±3 km in the continental crust where oxidizing, low-T, fluid-rich conditions are common. Subsequently, the clast was ejected from the Earth during a large impact, entrained in the lunar regolith as a terrestrial meteorite with the evidence of reducing conditions introduced during its incorporation into the Imbrium ejecta and host breccia.